Strategi Peningkatan Kewirausahaan dan Bisnis Dalam Perspektif Manajemen Islam Sebagai Kehidupan yang Menghidupi - Mirza Mahendra Siregar; Chuzaimah Batubara (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Business management and entrepreneurship have gained attention in the field of study due to the ever-changing global business environment, where culture and religion play a significant role in establishing business connections. The main purpose of this article is to analyze the shift of Islamic Change Management, as a religious concept, towards entrepreneurship and business. By utilizing up-to-date and relevant literature on the subject, this article draws upon the lessons of the Holy Quran and the customs. of Muhammad (S.AW). Studies focuses on themes such as piety, permissible and forbidden actions, knowledge and entrepreneurship, innovation and risk-taking, efficient resource utilization, financing, and an Islamic perspective on ethics and social responsibility. In conclusion, we propose further research directions and provide suggestions on how to approach the growing interest in this field of business management study. Additionally, we emphasize the influential role of the Islamic business context in driving entrepreneurial activity.